The Effect of Aromatherapy Treatment on Fatigue and Relaxation for Mothers during the Early Puerperal Period in Japan: A Pilot Study - Kyoko Asazawa; Yoshihiro Kato; Atsuko Yamaguchi; Asako Inoue (Shiraz University of Medical Sciences, 2017)
Background: Early in the postpartum period, mothers are often nervous and tired from the delivery, breast-feeding and caring for a new-born. The aim of this study was to evaluate the process and outcome of using aromatherapy treatments to increase relaxation and decrease fatigue for mothers during the first to the seventh day of the postpartum period. Methods: This non-randomized controlled study with a quasi-experimental one-group pretest-posttest design was used to evaluate scores in relaxation and fatigue before and after the intervention. Aromatherapy hand treatments were performed on a purposive sample of 34 postpartum mothers in Tokyo, Japan, from May to July 2016. The single treatment included a choice of one of five essential aroma oils through hand and forearm massage. Relaxation and fatigue were measured by self-administered valid and reliable questionnaires. Wilcoxon signed-rank test was conducted to analyze the data before and after the intervention. The software programs SPSS, v. 23.0 (SPSS, Tokyo), was used to analyze the data, with the significance level set at 5%. Results: Valid responses were obtained from 29 participants. A comparison of the scores before and after aroma treatment intervention indicated that the participants' relaxation scores increased significantly (P<0.001) and fatigue scores were significantly reduced (P<0.001). The majority of participants (77.8%) were satisfied with the treatment. Conclusion: The aroma treatments significantly improved relaxation and reduced fatigue for mothers in the early puerperal period and were well received. Therefore, a larger study using a pretest-posttest random control trial is recommended.